2000
DOI: 10.1046/j.1439-037x.2000.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Seed Coat Development in the Natural Tetraploid Trifolium pratense L.

Abstract: Seed coat development in the natural tetraploid Trifolium pratense L. was studied by electron microscopy. The mature seed coat derived from the outer integument is composed of three layers of cells. The cells of the outer epidermis divide anticlinally and undergo radial elongation to form a macrosclereid layer. The cells are characterized by thin walls, the presence of amyloplasts, and numerous vacuoles which are completely or incompletely filled with tannin. The outer tangential walls are thickened at an earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…A significant reduction of LM5 and LM6 epitopes in the cell walls of the mature seeds suggests that the loss of the galactan and the arabinan in the cell walls reflects remodeling of the cell wall during the abscission and that the cell wall compositional changes occur prior to the visibly recognizable abscission [3]. Both the PL and the CPL have been shown to strengthen the attachment of the seed to the funicle [18]. The loss of the LM5 galactan and the LM6 arabinan epitopes during the abscission process may suggest a clue for double palisade layers in their structural role in the abscission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant reduction of LM5 and LM6 epitopes in the cell walls of the mature seeds suggests that the loss of the galactan and the arabinan in the cell walls reflects remodeling of the cell wall during the abscission and that the cell wall compositional changes occur prior to the visibly recognizable abscission [3]. Both the PL and the CPL have been shown to strengthen the attachment of the seed to the funicle [18]. The loss of the LM5 galactan and the LM6 arabinan epitopes during the abscission process may suggest a clue for double palisade layers in their structural role in the abscission.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a spontaneous def mutant [17] has the seed strongly attached to the funicle and the subtending seed does not abscise from the funicle at any point in time. The double palisade layers have been suggested to play a structural supporting role in the attachment of the seed to the funicle [18]. …”
Section: Introductionmentioning
confidence: 99%
“…The lumen of macrosclereids is usually irregular and tapered toward the seed coat surface due to prominent cell wall thickening. Macrosclereids differentiation was followed in cytological detail in pea (Spurny, 1963; Harris, 1983), soybean (Harris, 1987), and clover (Algan and Büyükkartal, 2000). The length of macrosclereids seems to be under environmental control in soybean (Noodén et al, 1985).…”
Section: Legume Seed Coat (Testa) Development and Structurementioning
confidence: 99%
“…Sclereids are characterized by extensive secondary cell wall formation and are usually non-living at maturity with a callose-rich wall area running parallel to the edge of the seed coat (Bhalla and Slattery, 1984; Serrato Valenti et al, 1993; Ma et al, 2004). In common bean, cell vacuoles of the thick-walled epidermal cells are often completely filled with tannins, indicating that the macrosclereid cells play a key role in hardening of the seed coat (Algan and Büyükkartal, 2000). The contrasting cellular fates above are related to different functional requirements during the course of development: nutrient transport and metabolism to sustain embryo growth during embryogenesis and seed filling and physical and structural requirements as the seed matures to insure protection.…”
Section: Development and Accumulation Of Main Components Of The Testamentioning
confidence: 99%
“…The seeds of this genus were also reported to be diverse in their weight, dimensions, and shape. And and Büyükkartal (2000) also studied ultrastructural variation in the seed coat of T . pratense and found that the outer layer of the seed coat is made up of macrosclereids cells which appear elongated.…”
Section: Discussionmentioning
confidence: 99%